MERCOSUR: problems and prospects - Manzetti, Luigi ([s.n.] [S.l.])
Reviews the recent literature on integration theory and trade blocs. Describes the characteristics of a 'South-South' type of economic integration such as MERCOSUR and its results to date. Analyzes those factors that theoretically and practically prevent MERCOSUR from becoming an effective common market.